Knowledge, Attitude, Pictorial Health Warnings And Quitting Attempt To Smoking In Sarawak, Malaysia - Md Mizanur Rahman; Mohd Taha Arif; Mohd Raili Bin Suhaili; Mohd Fadzillah Abd Razak; Cliffton Akoi; Nor Zam Azihan; Nanthakumar (Bangladesh Academy of science, 2024)
Indexed by SCOPUS